A compact UHF RFID tag antenna for soil monitoring - Ismail, Muhammad Zamani; Ripin, Nabilah; A. Rahim, Mohamad Kamal; Ahmad, Nur Azliza (2024)
UHF RFID technology is currently being chosen to replace the existing soil monitoring system for smart agriculture. However, when attached to backing objects, the current RFID tag typically has a large footprint and a short read distance. Therefore, this paper introduces a compact tag antenna design comprising a slotted radiating patch connected to a ground plane via an inductive stub. The tag antenna is mounted on loamy soil for soil monitoring purposes. The proposed tag has a small size of only 48.2 48.2 mm, a power transmission coefficient of 0.99, and a longer theoretical read range of 9m